Static mechanical, interfacial, and water absorption behaviors of alkali treated oil palm mesocarp fiber reinforced poly(butylene succinate) biocomposites - Then, Yoon Yee; Ibrahim, Nor Azowa; Zainuddin, Norhazlin; Ariffin, Hidayah; Wan Yunus, Wan Md Zin; Chieng, Buong Woei (North Carolina State University, 2015)
In this work, oil palm mesocarp fiber (OPMF) was surface-treated with varying NaOH concentrations (1, 3, 5, 7, or 9%) and soaking times (1, 2, 3, or 4 h) at room temperature aiming to enhance its adhesion to the thermoplastic matrix for biocomposite application. The biocomposites from alkali treated OPMFs and poly(butylene succinate) at weight ratios of 70:30 were fabricated by a melt blending technique and hot-pressed moulding. The results indicate that NaOH treatment removed fiber’s surface waxes, hemicellulose, and lignin, and produced fiber with rough surface morphology. The tensile results showed that OPMF treated in 5% NaOH solution for 3 h produced biocomposite with enhanced tensile strength (30%), tensile modulus (105%), and elongation at break (16%), as well as reduced water absorption (15%) and thickness swelling (13%) in comparison to that of untreated OPMF. Scanning electron microscopy showed improvement of interfacial adhesion between treated fiber and poly(butylene succinate). These results suggest that NaOH treatment could be an effective form of treatment for OPMF in biocomposites materials.